Business Process Reengineering ANALISA BUSINESS PROCESS REENGINEERING PADA PELAYANAN ADMINISTRASI DI KANTOR KECAMATAN NGEBEL KABUPATEN PONOROGO PROVINSI JAWA TIMUR INDONESIA: . - Fibi Chandra Puspita; Suwardi Suwardi; Herning Suryo Sardjono (Master of Public Administration, Universitas Slamet Riyadi, 2023)
This study aims to analyze problems and design procedures for administrative services at the Ngebel District Office, Ponorogo Regency. This research was conducted by interview, observation, and documentation. Informants as sources of data in this study are internal informants (service providers) and external informants (service users). The method used in determining the data source is purposive sampling method. The results of this study indicate that based on the results of fishbone/cause-effect analysis and value added analysis on administrative services held, classical problems are still found. The administrative service procedure analyzed has a Value Added Ratio of around 86.36% so that it can still be improved. The existing problems require re-engineering of administrative service business processes so that it will support the achievement of effective and efficient administrative service goals. Analysis of the results of business process reengineering using Business Impact Analysis obtained 21 positive values ​​and 8 negative values ​​so that the results of business process reengineering are feasible to continue with their implementation. Keywords : business process reengineering, administrative service, government process reengineering